A Comparative Analysis of Financial Performance and Stability Between Indonesian Sharia Bank (BSI) and Bank Mandiri From 2020 to 2024 - Jamaludin, Jamaludin; Aspiranti , Tasya; Amaliah, Ima; Nurhayati, Nunung; Lestari, Rini (International Journal of Science, Technology & Management, 2026)
This study aims to assess and describe the financial performance of Bank Mandiri and Indonesian Sharia Bank (BSI) based on the RGEC analysis results during the period 2020–2024. The research method used is quantitative with a descriptive quantitative approach. The population of the study includes all banks registered and operating in Indonesia during the 2020–2024 period, or more specifically certain banks such as conventional banks and sharia banks. The samples selected are Bank Mandiri as the representative of conventional banks and Indonesian Sharia Bank (BSI) as the representative of sharia banks for the 2020–2024 period. The sample selection is based on relevance, availability of data, and representation of each bank type. The results show that Bank Mandiri demonstrates superior performance compared to Indonesian Sharia Bank (BSI) on most key RGEC indicators. Bank Mandiri maintains asset quality with significantly lower NPF, as well as records better efficiency in asset and capital utilization through higher ROA and ROE. Additionally, Mandiri’s operating margin (NOM) is much stronger and more stable. Although both banks have very strong capital adequacy (CAR) and good governance (GCG), operational efficiency (BOPO) remains a challenge for both, even though BSI shows slightly better BOPO figures. Overall, Mandiri is more aggressive in financing distribution and efficient in generating profit, while BSI is still in the process of post-merger stabilization with reasonably healthy performance but with room for improvement in operating margin and efficiency.